Importancia de la correcta redacción periodística para la divulgación de noticias en medios tradicionales de la ciudad de Quevedo - Cabrera Mora, Angel Eloy (2021)
This research was carried out in the city of Quevedo in order to determine the importance of correct journalistic writing for the dissemination of news in traditional media in the city of Quevedo, it is intended that this study will achieve a better dissemination of news in said media. In the theoretical support there are empirical bases that support the veracity of the same, making this a sustainable study. For the methodology, the mixed modality was used, that is, qualitative and quantitative, and its research was descriptive, the technique used to obtain data, was the virtual survey which was carried out through Google form to professional communicators and residents of the city of Quevedo. The conclusions that were reached is that journalistic writing is definitely important in the journalistic field, that techniques that improve writing should be applied before publishing the news.